Structural effects of halogen bonding in iodochalcones. Issue 3 (13th May 2021) - Hamilton, Victoria; Harris, Connah; Hall, Charlie L.; Potticary, Jason; Cremeens, Matthew E.; D'Ambruoso, Gemma D.; Matsumoto, Masaomi; Warren, Stephen D.; Pridmore, Natalie E.; Sparkes, Hazel A.; Hall, Simon R.
Abstract : The structures of three iodochalcones are presented, highlighting the dependence of intermolecular bonding on the functionalization of their aromatic rings. Abstract : The structures of three iodochalcones, functionalized with fluorine or a nitro group, have been investigated to explore the impact of different molecular electrostatic distributions on the halogen bonding within each crystal structure. The strongly withdrawing nitro group presented a switch of the halogen bond from a lateral to a linear motif. Surprisingly, this appears to be influenced by a net positive shift in charge distribution around the lateral edges of the σ‐hole, making the lateral I…I bonding motif less preferable. A channel of amphoteric I…I type II halogen bonds is observed for a chalcone molecule, which was not previously reported in chalcones, alongside an example of the common synthon involving extended linear chains of I…O2 N donor–acceptor halogen bonds. This work shows that halogenated chalcones may be an interesting target for developing halogen bonding as a significant tool within crystal engineering, a thus far underexplored area for this common structural motif.